2001
DOI: 10.1007/s00417-001-0384-4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of lymphatic drainage system in corneal allograft rejection in mice

Abstract: Our data confirm the existence of functional lymphatic drainage via the uveoscleral pathway and conjunctiva in the mouse. Cells within the ipsilateral submandibular lymph node respond to stimuli upstream. This reaction could potentially be manipulated to improve graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…The production of IFN-␥ by T cells in these same SMLNs was also induced following allogeneic corneal transplantation implicating SMLN in corneal rejection (66). However, in a separate study, corneal graft survival was greatly enhanced by the excision of superficial CLN and FLN but not SMLN (67,68).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The production of IFN-␥ by T cells in these same SMLNs was also induced following allogeneic corneal transplantation implicating SMLN in corneal rejection (66). However, in a separate study, corneal graft survival was greatly enhanced by the excision of superficial CLN and FLN but not SMLN (67,68).…”
Section: Discussionmentioning
confidence: 88%
“…The presence of Ag ϩ cells in the subcapsular sinus of the draining LNs (SMLN, FLN, and CLN), in contrast, indicate that at least a portion of the Ag placed in the AC somehow gains access to lymph vessels in the head and neck. Although it is generally accepted that the internal compartments and uveal tract of the eye are devoid of lymphatic drainage, recent evidence suggests that a connection between the eye and local LNs exists (8,10,65,66). Melanoma cells placed in the AC (9) gain access to LNs in the neck suggesting that a similar connection exists for nonsoluble cell-associated Ags.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in a few studies that antigen presenting cells that have been derived from the eye can be directly drained to the spleen via blood (Wilbanks and Streilein,1990Wilbanks et al, 1991). Despite this belief that antigens of the anterior humor can directly drain into the blood without any anatomical lymphatic drainage, it has been demonstrated that soluble antigens reach the lymph nodes in the neck after injections into the anterior chamber (Hoffman et al, 2001;Boonman et al, 2004;Camelo et al, 2006;Yücel et al, 2009). This suggests that the lack of an effective immune response to intraocular antigens is not due to an inability to recognize intraocular antigens, but rather a lack of an effective immune response to develop and persist after antigen recognition or peripheral tolerance.…”
Section: Immunological Perspectivementioning
confidence: 99%
“…An alternative route through interstitial spaces, the uveoscleral outflow, enables part of the aqueous humor (ϳ16%) (39) to escape into the extraorbital conjunctival tissues (40,41). This route of drainage was first identified in studies from the 1960s of human and monkey eyes (40,41), but the exact path or paths of the outflow have not been well defined.…”
Section: Routes Of Ag Out Of the Eyementioning
confidence: 99%